The relationships between service quality, satisfaction, and loyalty of spa customers/ Siti Nadhirah Mohamad, Hasif Rafidee Hasbollah and Siti Fatimah Ab Ghaffar - Mohamad, Siti Nadhirah; Hasbollah, Hasif Rafidee; Ab Ghaffar, Siti Fatimah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Post pandemic era, spa has been evolved in a rapid growth with a high demand services in Malaysia. Therefore, the customer of hotel and resort spa have a high expectations of services in this wellness industry. However, due to some deficit in this service quality affect the customer's service expectation. The aim of this paper is to the determine the relationship between spa service quality and customer satisfaction and loyalty among hotel and resort spa customers. A cross-sectional study will be conducted among spa customers in Kelantan. Convenience sampling method will be applied as sampling method and a set of online questionnaires will be used for data collection. From customer perspective, the service quality, customer satisfaction and loyalty will be measured. Multiple linear regression analysis will be performed to determine the relationships between variables. The expected findings will be there are significant association between the service quality and customer satisfaction and loyalty among hotel and resort spa customers. This information will be useful to contribute to the body of knowledge on spa services quality. Moreover, it also beneficial for spa managers to redesign the strategies to improve services quality in hotel and resort spa.